Association of Leptin With Mortality in Patients on Maintenance Hemodialysis: a Prospective Study (Iranian Journal of Kidney Diseases, 2014)
Introduction. Prior studies evaluating the relationship between leptin and outcomes in chronic kidney disease patients have shown conflicting results. Our aim was to evaluate the association of serum leptin with all-cause and cardiovascular disease (CVD)-related mortality in stable maintenance hemodialysis patients. Materials and Methods. We carried out an observational prospective cohort study of 53 patients on maintenance hemodialysis. The follow-up period was 5 years. Leptin levels were measured at baseline before the start of a hemodialysis session. Proportional hazards models were used to evaluate the relationship between leptin and all-cause and CVD-related mortality. Results. During the follow-up period, 26 patients (49.1%) died. Fifteen of 26 deaths (57.7%) were attributable to CVD. Cox proportional hazards analysis showed that a leptin level equal to or greate than the median value (3.45 ng/mL) was associated with lower mortality rates (hazard ratio, 0.211; 95% confidence interval, 0.062 to 0.723; P = .01) after multivariable adjustment for potential confounders. However, leptin was not an independent risk factor for CVD-related mortality. Conclusions. There was a converse association between the serum leptin concentration and mortality in stable maintenance hemodialysis patients. Low serum leptin concentration is an independent risk factor of all-cause mortality in stable maintenance hemodialysis patients, but may not be linked with CVD-related mortality.